2012
DOI: 10.1016/j.neuron.2011.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Sound-Driven Synaptic Inhibition in Primary Visual Cortex

Abstract: SummaryMultimodal objects and events activate many sensory cortical areas simultaneously. This is possibly reflected in reciprocal modulations of neuronal activity, even at the level of primary cortical areas. However, the synaptic character of these interareal interactions, and their impact on synaptic and behavioral sensory responses are unclear. Here, we found that activation of auditory cortex by a noise burst drove local GABAergic inhibition on supragranular pyramids of the mouse primary visual cortex, vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
389
16

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(446 citation statements)
references
References 63 publications
(75 reference statements)
41
389
16
Order By: Relevance
“…In agreement with this notion are data from animals demonstrating auditory as well as somatosensory cross-modal convergence within visual cortex of monkeys Wang et al, 2008), cats (Murata et al, 1965;Spinelli et al, 1968;Morrell, 1972;Majkowski and Sobieszek, 1972;Fishman and Michael, 1973), and mice (Iurilli et al, 2012). For example, Iurilli et al (2012) showed that auditory inputs suppressed visual responses within infragranular layers of primary visual cortex via GABAergic synapses and moreover that this suppression was directly linked to performance (as measured by a conditioned motor response). These authors suggested that auditory inputs degrade the perception of the visual stimulus; something that will need to be reconciled with the many studies showing multisensory and cross-modal enhancement of perception and behaviour (a sampling of which we review here).…”
Section: Electromagnetic Signals (Eeg/meg)mentioning
confidence: 53%
See 2 more Smart Citations
“…In agreement with this notion are data from animals demonstrating auditory as well as somatosensory cross-modal convergence within visual cortex of monkeys Wang et al, 2008), cats (Murata et al, 1965;Spinelli et al, 1968;Morrell, 1972;Majkowski and Sobieszek, 1972;Fishman and Michael, 1973), and mice (Iurilli et al, 2012). For example, Iurilli et al (2012) showed that auditory inputs suppressed visual responses within infragranular layers of primary visual cortex via GABAergic synapses and moreover that this suppression was directly linked to performance (as measured by a conditioned motor response). These authors suggested that auditory inputs degrade the perception of the visual stimulus; something that will need to be reconciled with the many studies showing multisensory and cross-modal enhancement of perception and behaviour (a sampling of which we review here).…”
Section: Electromagnetic Signals (Eeg/meg)mentioning
confidence: 53%
“…Because source estimations were performed after first Raij et al, 2010), suggesting that pathways for convergence may be the same as those generating interaction effects (although this remains to be more thoroughly examined; reviewed in Meredith et al, 2009 andvan Atteveldt et al, 2014a). In agreement with this notion are data from animals demonstrating auditory as well as somatosensory cross-modal convergence within visual cortex of monkeys Wang et al, 2008), cats (Murata et al, 1965;Spinelli et al, 1968;Morrell, 1972;Majkowski and Sobieszek, 1972;Fishman and Michael, 1973), and mice (Iurilli et al, 2012). For example, Iurilli et al (2012) showed that auditory inputs suppressed visual responses within infragranular layers of primary visual cortex via GABAergic synapses and moreover that this suppression was directly linked to performance (as measured by a conditioned motor response).…”
Section: Electromagnetic Signals (Eeg/meg)mentioning
confidence: 90%
See 1 more Smart Citation
“…7). In other words, synaptic scaling in A1, induced by CHL, restored the cross-modal effects of A1 on V1, which are typically mediated by an intact A1 30,47 . These data suggest that synaptic scaling acts to restore the precise function of neuronal networks without losing information.…”
Section: Discussionmentioning
confidence: 93%
“…Accumulating evidence suggests that audiovisual modulations are largely based on modulation of temporal processing, not changes in the overall response amplitudes (Allman et al 2008, Iurilli et al 2012, Lakatos et al 2007. For instance, when monkeys are presented with naturalistic sounds accompanied with matching visual stimulus, firing rate of the neurons in the auditory cortex and inter-trial variability of the activation is decreased (Dahl et al 2010).…”
Section: Brain Areas Involved In Audiovisual Modulationsmentioning
confidence: 99%